PERANCANGAN APLIKASI PERSEDIAAN BAHAN KUE BERBASIS WEBSITE MENGGUNAKAN METODE PROTOTYPE PADA DAPUR ALLYSA - Prastiawan; Risah Subariah (Lembaga Pengembangan Kinerja Dosen, 2023)
Allysa's Kitchen is a home-based business that operates in the service sector and produces various kinds of cakes ranging from home-made cakes to traditional cakes. Currently, Allysa's Kitchen is still keeping records and reporting supplies of cake ingredients using memos. So that it is vulnerable to loss of data and ineffectiveness of the information carried out. The research based on these problems is the background for designing cake-based material inventory applications website which can facilitate data processing with systems that are integrated intodatabase so that the recording of the flow of incoming goods, outgoing goods and reports can be operated quickly and accurately. The system development method applied is the method prototype. Prototype is a system developer's technical method for describing the system to the owner so that he has a clear picture of the system to be built by the developer. Advantages of the method prototype compared to other developer methods namely high time efficiency in system development and easier to implement. For designing, use HTML, PHP, and Java Scrip as well as MySQL as the database. Testing in this application uses blackbox testing and whitebox testing. The results of this study are awebsite which can make it easier for owners to manage cake ingredients stock and manage reports